PENGARUH KECERDASAN EMOSIONAL, PERILAKU BELAJAR DAN MINAT BELAJAR TERHADAP PEMAHAMAN AKUNTANSI (STUDI PADA MAHASISWA AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS NUSA CENDANA) - Theodora Vivinia Ndait; Minarni Anaci Dethan; Sarlin Paleina Nawa Pau (Universitas Nusa Cendana, 2022)
The purpose of this research is to know the effect of emotional intelligence, learning behavior and learning interest towards the understanding of accounting partially and simultaneously. The technique of analysis used in this research is multiple linear regression. The data was collected by quesionnare. Sample used in this research is 135. The results of this research showed that partially emotional intelligence has no effect towards the understanding of accounting, whereas learning behavior and learning interest affect the understanding of accounting. The result of this research simultaneously showed that emotional intelligence, learning behavior and learning interest affect the understanding of accounting